325. Invasive and Non-Invasive Osteomyelitis Caused by Group B Streptococcus Infection Among Veterans. (31st December 2020) - Bej, Taissa A; Wilson, Brigid; Banks, Richard; Briggs, Janet; Song, Sunah; Perez, Federico; Jump, Robin
Abstract: Background: Epidemiological studies that assess invasive Group B Streptococcus (GBS) infections may not capture cases of osteomyelitis diagnosed using non-invasive cultures in combination with imaging, laboratory tests, and clinical assessment. Here, we compare GBS osteomyelitis among individuals diagnosed using invasive and non-invasive cultures. Methods: Using the Veterans Health Administration corporate data warehouse, we studied a national retrospective cohort review of Veterans diagnosed with GBS osteomyelitis between 2008 – 2017. Invasive cases were defined as an International Classification of Disease (ICD) code for osteomyelitis accompanied by a blood or bone culture positive for GBS within 2 weeks. Non-invasive cases were defined as an ICD code for osteomyelitis and a non-invasive culture positive for GBS from a concordant site within 2 weeks. We compared demographics, comorbid conditions, mortality, and time to below- or above-knee amputation among patients with invasive and non-invasive GBS osteomyelitis. Results: We identified 1167 cases of invasive osteomyelitis among 1077 patients and 692 cases of non-invasive osteomyelitis among 644 patients. Most patients were male (98%) with an average age of 63.2 years (± standard deviation (SD) 10.1 years). The Charlson Comorbidity Index (CCI) was similar among patients with invasive and non-invasive disease (3.85 ± SD 2.3 and 3.83 ± SD2.4, respectively). Among those with lower extremity osteomyelitis, 11% of invasive cases had an amputation at 30 days while 2% of non-invasive cases had an amputation in the same time frame (Figure 1 ). Mortality was similar among those with invasive and non-invasive GBS osteomyelitis at 30-days (1% and 1%, respectively) and at 1-year (11% and 9%, respectively) (Figure 2 ). Figure 1: Time to Amputation Figure 2: Survival Conclusion: Over 1/3 of the cases of osteomyelitis caused by GBS do not meet the case definition for invasive disease. Whether diagnosed using invasive or non-invasive microbiological cultures, survival outcomes for people with GBS osteomyelitis were similar. These findings suggest that non-invasive GBS osteomyelitis is as clinically important as invasive GBS osteomyelitis and that the rates of GBS osteomyelitis may be higher than previously reported. Disclosures: Federico Perez, MD, MS, Accelerate (Research Grant or Support)Merck (Research Grant or Support)Pfizer (Research Grant or Support) Robin Jump, MD, PhD, Accelerate (Grant/Research Support)Merck (Grant/Research Support)Pfizer (Grant/Research Support, Advisor or Review Panel member)Roche (Advisor or Review Panel member)